LEARNING BY LIVING: ACCULTURATION, LEADERSHIP, AND REFLEXIVITY IN BANCEUY’S INFORMAL ADULT EDUCATION ECOSYSTEM - Budi Yasri; Vera Firmansyah; Dudi Adi Firmansyah; Sri Nurhayati; Gianto Gianto; Disa Aisha Mutmainnah; Fatima Zahra Lotfi; Damola Olugbade; Md. Hafizi Ahsan; Gumpanat Boriboon (Prima Magistra: Jurnal Ilmiah Kependidikan, 2025)
Despite increasing recognition of Indigenous knowledge systems, the role of informal adult learning within customary communities remains under-theorized in mainstream adult education discourse. There is limited understanding of how traditional practices, beliefs, and community structures shape learning processes outside formal institutions. This study investigates the role of informal adult learning in Kampung Adat Banceuy, a Sundanese customary village in West Java, Indonesia. The research focuses on how learning is embedded in four interconnected domains: customary leadership, ritual practice, selective acculturation, and community-based tourism. These domains form a cohesive learning ecology through which cultural knowledge, social roles, and ethical values are transmitted and adapted across generations. Using an ethnographic methodology, the study involved participant observation, semi-structured interviews with 36 informants, and analysis of cultural documents. Data were examined through thematic coding and interpretive analysis to capture the nuanced, situated processes of learning as enacted in everyday life. Findings show that informal adult learning in Banceuy is relational, embodied, and performative. Tourism, in particular, functions as a reflexive learning environment where adults develop narrative, logistical, and intercultural competencies while negotiating cultural meaning and ethical boundaries. Rather than being a site of commodification, tourism becomes a space of identity work and adaptive pedagogy. These insights challenge conventional hierarchies of formal education and affirm the centrality of Indigenous learning systems in sustaining cultural resilience. The study offers implications for policy and theory, emphasizing the need to support culturally embedded, community-driven models of adult education.